Generating Income from Nepal’s Community Forestry: Does Timber Matter? - Pokharel, Ridish K (Journal of Forest and Livelihood, 2013)
This paper argues that timber is the most valuable product of community forests and forms the largest share of the income for community forest user groups (CFUGs). This paper assesses the sources of CFUGs’ income in general and income through timber sale, in particular. Drawing information from one hundred CFUGs in three mid-hill districts of Nepal, shows that the contribution from timber is significantly higher compared to other sources such as non- timber forest products, membership fee, penalty, and renting meeting hall. Moreover, the CFUGs with timber sale collect a lesser amount of membership fee, which is one of the major incentives for the members. The research findings emphasize the need to put timber in CFUGs’ key forest management priority. DOI: http://dx.doi.org/10.3126/jfl.v9i1.8588 Journal of Forestry and Livelihood Vol.9(1) 2010 16-20